1981
DOI: 10.1172/jci110090
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of prostacyclin production by de-endothelialized rabbit aorta. Critical role of neointimal smooth muscle cells.

Abstract: A B S T R A C T Prostacyclin (PGI2) synthetic capacity was assayed at the surface of aortas at various intervals after removal of endothelium with a balloon catheter. Results were correlated with morphologic changes in the vessel wall seen by light microscopy, scanning and transmission electron microscopy. To assay PGI2 synthetic capacity, we applied an incubation chamber to the luminal surface of the aortas; after arachidonic acid stimulation we assayed the PGI2 synthesized with a bioassay and radioimmunoassa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
45
0
1

Year Published

1984
1984
2005
2005

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(50 citation statements)
references
References 30 publications
(30 reference statements)
4
45
0
1
Order By: Relevance
“…3 Because PGI 2 formed by the deeper layers of the media normally does not reach the luminal surface, endothelial tissue is responsible for nearly all PGI 2 at this critical interface of platelet-vessel wall interaction. 4 The usual source of substrate for PGI 2 production appears to be intracellular pools of esterified fatty acid within the endothelium; upon synthesis, it is released immediately from the cells, so that synthesis is synonymous with release. 48 Skidgel and Printz 36 reported that rat arteries generated greater quantities of PGI 2 than did veins and further postulated a segmental distribution of PGI 2 synthetase activity in blood vessels.…”
Section: Resultsmentioning
confidence: 99%
“…3 Because PGI 2 formed by the deeper layers of the media normally does not reach the luminal surface, endothelial tissue is responsible for nearly all PGI 2 at this critical interface of platelet-vessel wall interaction. 4 The usual source of substrate for PGI 2 production appears to be intracellular pools of esterified fatty acid within the endothelium; upon synthesis, it is released immediately from the cells, so that synthesis is synonymous with release. 48 Skidgel and Printz 36 reported that rat arteries generated greater quantities of PGI 2 than did veins and further postulated a segmental distribution of PGI 2 synthetase activity in blood vessels.…”
Section: Resultsmentioning
confidence: 99%
“…The chamber excludes cut tissue edges from study and has previously been shown to measure release of PGI2 released from endothelium rather than from smooth muscle layers of the vessel wall. 26 The chambers were designed and made available by Dr. Eric Grabowski.…”
Section: Methodsmentioning
confidence: 99%
“…HDL and LDL are also present in interstitial fluid and in lymph (Roheim et al, 1976 (Eldor et al, 1981). However, medial smooth muscle cells migrate through the internal elastic membrane and proliferate to form a neointima; these cells are capable of synthesizing PGI 2 and are in direct contact with plasma HDL and LDL (Eldor et al, 1981).…”
mentioning
confidence: 99%
“…Both HDL and LDL are normally transported through the intact endothelium of blood vessels by the process of diacytosis and come into contact with vascular smooth muscle cells present in the media Leake andaggregation can initiate the formation of experimental atherosclerotic lesions, prostaglandin formation is initially reduced (Eldor et al, 1981). However, medial smooth muscle cells migrate through the internal elastic membrane and proliferate to form a neointima; these cells are capable of synthesizing PGI 2 and are in direct contact with plasma HDL and LDL (Eldor et al, 1981).…”
mentioning
confidence: 99%
See 1 more Smart Citation